So many words: indexing oral history. (December 2016) - Newberry, Mary; de Boer, Margaret; Robinson, Frances; Watt, Stephanie; Peace, Alexandra
Abstract : Mary Newberry and her colleagues describe their team effort to index an oral history project on Mary's neighbourhood, discussing the strategies they developed for making the indexing quick and doable by a number of people, largely volunteer, while maintaining some cohesiveness.